PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN RAINBOW SPIN TERHADAP KECERDASAN VISUAL SPASIAL PADA ANAK USIA 4-5 TAHUN DI TK AL-HIDAYAH GAMPONG ARAFAH SAMADUA - Asih Gusnida; Nurzanah (CV. ADIBA ASIHA AMIRA, 2023)
Background: The role of media in learning is a physical tool that stores messages and can stimulate children in learning and is used for the teaching and learning process. Therefore, the role of media is very helpful for teachers to facilitate the delivery of material to children. One of the learning media that is still minimally used as a learning media is rainbow spin media. The use of rainbow spin media is able to make learning easier for kindergarten children and children can use learning media to be more innovative, creative and so that problems faced by children and teachers can be resolved. Objectives: This study aims to determine the effect of using rainbow spin learning media on visual spatial intelligence in children aged 4-5 years. Method: the method used in this research is experimental research with a pre-experimental design because it only involves one class as an experimental class which is carried out without any groups. The sampling technique in this research used purposive sampling which was carried out at the Al-Hidayah Gampong Arafah Samadua Kindergarten with a sample size of 15 people. Results: This research shows that the use of rainbow spin is able to develop children's visual spatial intelligence at the Al-Hidayah Gampong Arafah Samadua Kindergarten. The significance of the increase in children's visual spatial intelligence development scores was shown between before and after learning using rainbow spin media. Suggestion: So that teachers and schools can apply Rainbow Spin media in learning to increase teachers' insight and creativity in developing learning media and can develop children's cognitive intelligence well